RISK FACTORS FOR DIARRHEA IN NOEBEBA DISTRICT, TIMOR TENGAH SELATAN REGENCY - Denisius Umbu Pati (Jurnal Kesehatan Tambusai, 2023)
One frequent cause of diarrhea caused by poor sanitation and behavior. This study aimed to analyze the factors affecting the incidence of diarrhea in the district of Timor Tengah Selatan regency Noebeba. This type of research conducted in this research is analytic survey with cross sectional study design. Noebeba research location in the district of South Central Timor. The population is all the people residing in the District Noebeba 3186 amounted to housewives, the technique of sampling using random sampling (simple random sampling) and samples are 355 housewives. Results of univariate analysis showed that, with diarrhea in the district Noebeba amounted to 78 (22.0%) and diarrhea amounted to 277 people (78%). The results of the bivariate analysis showed that there is a relationship between a container of household water (p = 0.003), the condition of latrines (p = 0.000), housewife knowledge (p = 0.000), and the practice of hand washing (p = 0.001) and the incidence of diarrhea. However, the results also showed that there is no correlation between the condition of household trash (p = 0.262) and sanitation of food (p = 0.156) and the incidence of diarrhea. It is also necessary cross-sector efforts to empower communities by engaging governments and NGOs that exist and make regulations relating to the behavior of clean and healthy living for people.